Advances in molecular engineering of organic-inorganic/inorganic halide perovskites: Photochemical properties behind the energy conversion ability. (December 2019) - Arkan, Foroogh; Izadyar, Mohammad
Graphical abstract: A comprehensive physical chemistry study on the properties of the perovskites shows that they can be applied as an acceptable benchmark in design of PVSCs. Highlights: Organic-inorganic/inorganic halide ABX3 perovskites were investigated, theoretically. Cation, anion, and halide affects the efficiency of the perovskite solar cells. I-based perovskites have a greater activity of nonlinear optic performance. Cs +, Rb +, and Az + -based perovskites are proposed as the most promising candidates. Abstract: Here, molecular engineering of the organic-inorganic/inorganic halide perovskites indicates the role of cation, anion and halide components on the efficiency of the perovskite solar cells (PVSCs). The frontier molecular orbitals alignment of the ABX3 perovskites (A = Im; Imidazolium, Az; Azetidinium, Hy; Hydrazinium, Cs, Rb, Tl, B = Pb, Sn, Ge, X = Br, Cl, I) showed a balanced electron-hole transfer. The cation and halide ion are the main parts of the charge transfer from the dynamic viewpoint, while the exciton formation/dissociation rates, Rd / Ra, are mainly affected by BX3 anion. In addition to Cs + and Rb +, Im + -based perovskites show an effective charge transfer distance and electron-hole (e-h) overlap, which makes them good excitation modes. I-based perovskites represent a higher response to the electric field, originated from their less electronic chemical harness. According to final efficiency, Cs +, Rb +, and Az + -based perovskites are introduced as the best photosensitizers.